2017
DOI: 10.1021/acs.jpcc.7b06188
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Precipitation in Irradiated and Annealed Ceria Doped with Metals for Emulation of Spent Fuels

Abstract: Epsilon-phase alloy precipitates have been observed with varied compositions and sizes in spent nuclear fuels, such as UO2. The presence of the inclusions, along with other oxide precipitates, gas bubbles, and irradiation-induced structural defects, can significantly degrade the physical properties of the fuel. To predict fuel performance, a fundamental study of the precipitation processes is needed. This study uses ceria (CeO2) as a surrogate for UO2. Polycrystalline CeO2 films doped with Mo, Ru, Rh, Pd, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…A sequence of high-angle annular dark-field (HAADF) STEM images for the film under 20 min isochronal annealing at temperatures from 873 to 1373 K are shown in Figure . Our previous study showed formation of small Pd particles (∼3 nm in size) in the as-irradiated film. Those particles are not visible in the low magnification image of Figure a.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…A sequence of high-angle annular dark-field (HAADF) STEM images for the film under 20 min isochronal annealing at temperatures from 873 to 1373 K are shown in Figure . Our previous study showed formation of small Pd particles (∼3 nm in size) in the as-irradiated film. Those particles are not visible in the low magnification image of Figure a.…”
Section: Resultsmentioning
confidence: 92%
“…In fact, the calculated atomic ratio of Ru to Mo is 0.80 for 43 GW d/t U after 100 years cooling time as compared to 0.75 in this study. Pd has been found to be the most mobile element among the five dopants in CeO 2 . Pd atoms can be clustered and precipitated to small particles at an elevated temperature, which then become immobile at higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study involving emulated spent fuel, Jiang et al [464] used TEM and APT to study thin films of CeO2 doped with metallic fission products. They found a uniform distribution of doped metals within the as-grown film.…”
Section: Precipitatesmentioning
confidence: 99%
“…A simple estimate using Shannon ionic radii 43 shows that a transition from eightfold-coordinated U 4+ (1 Å) → U 6+ (0.86 Å) amounts to a 14% ion size reduction, in line with the change from Ce 3+ (1.14 Å) → Ce 4+ (0.97 Å) of 17.5%. While CeO 2 possesses a fluorite structure very similar to UO 2 and is often used as a proxy to simulate radiation damage effects, 44,45 we expect even greater channeling behavior due to the higher atomic scattering factor of U (Z = 92) versus Ce (Z = 58). 46 As shown in supplementary Fig.…”
mentioning
confidence: 92%